Effect of gaming on behavioral intention to use online training: an adjustment of the UTAUT model applied to TRT-2 - Oliveira, Ludmilla Cavarzere de; Pinochet, Luis Hernan Contreras; Bueno, Ricardo Luiz Pereira; Oliveira, Mauri Aparecido de (Revista de Administração da UFSM, 2019)
The objective of this research was to analyze the effect of gamification on intention to use online training from the partial validation of the UTAUT model for qualification of members and servers of the Regional Labor Court of the 2nd Region (TRT-2). The study analyzed the relationship between constructs performance expectancy, effort expectancy, facilitating conditions, and familiarity with the intention to use gaming in distance media. This was conducted through an empirical application, which used the Structural Equation Modeling (SEM) for data analysis. The research was a single cross-sectional survey, carried out with TRT-2 members and servers who participated in the distance-feeding course ‘Healthy Living’ in 2015. Of the four hypotheses, only familiarity (F) was not significant as it did not serve as a behavioral intentions (BI) predictor of gamification for distance learning courses. Some explanations for such phenomenon may be career promotion and additional qualifications, learning by doing and sample size. The results confirmed that most hypotheses have a high statistical significance of the structural paths and have demonstrated that the model proposed in this study is consistent and can be applied in future studies with appropriate adjustments.